Assessing Children’s Mastery Motivation using the Dimensions of Mastery Questionnaire (DMQ): Theoretical and Practical Consideration - Amalina, Ijtihadi Kamilia (Central European Journal of Educational Research, 2022)
Bibliography of the reviewed book: Morgan, G. A., Liao, H.-F., & Józsa, K. (Eds.) (2020). Assessing Mastery Motivation in Children Using the Dimensions of Mastery Questionnaire (DMQ). Gödöllő: Szent István Egyetem. http://www.staff.u-szeged.hu/ jozsa/DMQbook.html